2019
DOI: 10.26501/jibm/2019.0902-014
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Banks’ Financing and Employment Generation: The Case of Punjab, Pakistan

Abstract: The purpose of this paper is to introduce h. alāl logo as a new marketing paradigm, which marketers use as a means of distinguishing their products and services in the competitive environment. This research aims to show the importance of education and training in the area of h. alāl and encouraging scientific societies as well as industry players for further research on the subject. We examine whether customers look for the h. alāl logo when purchasing products and services or whether know about the owner of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…These certifications are easy to find due to the likelihood of adulteration in foods of this type (Salman & Siddiqui, 2014). Giyahi and Khashei Varnamkhasti's (2019) studies with Iranian consumers showed that an effective branding strategy for HP is necessary.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These certifications are easy to find due to the likelihood of adulteration in foods of this type (Salman & Siddiqui, 2014). Giyahi and Khashei Varnamkhasti's (2019) studies with Iranian consumers showed that an effective branding strategy for HP is necessary.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Awareness of running a business and business actors who have access to Islamic financial institutions must provide more comprehensive benefits in the long term for micro-scale businesses with larger business volumes and have implications for the additional workforce (Benbekhti et al, 2021). In other experiences, it has the potential, and at a macro level, to support establishing Islamic microfinance institutions that provide easy, cheap and affordable access to financing and impact job creation (Malik & Ashraf, 2019).…”
Section: Introductionmentioning
confidence: 99%